Heavy Metal Pb, Cu, and Cd Pollution in Water and Sediment Due to Anthropogenic Activities Along the Musi River, South Sumatra - Wahyudi, Wahyudi; Rozirwan, Rozirwan; Putri, Wike Ayu Eka (Faculty of Mathtmatics and Natural Sciences, 2025)
Human activities along river flows can increase the potential for heavy metal pollution, which risks reducing water quality, polluting sediments, and threatening the sustainability of aquatic ecosystems. This research aims to evaluate the distribution of heavy metal pollution in water and sediment in the Musi River, which is affected by various anthropogenic activities. Samples for heavy metal analysis were collected from four clusters of observation locations. The heavy metal parameters tested included Cd, Cu, and Pb, which were analyzed using the wet digestion method and measured with an Atomic Absorption Spectrophotometer (AAS). The resulting heavy metal contaminations in sediment were much higher than in water, with Pb having the highest concentration in both matrices. Pb concentrations in sediment ranged from 11.845 to 15.301 mg/kg, while in water they ranged from 0.0791 to 0.0801 mg/L. Cu has more varied concentrations, with the highest value in Cluster 4 sediment of 9.518 mg/kg and water of 0.0160 mg/L. Meanwhile, Cd has a low but significant concentration, with values in sediment ranging from 0.130 to 0.315 mg/kg and in water from 0.0084 to 0.0101 mg/L. This heavy metal pollution shows that sediment functions as the main reservoir for heavy metals due to bioadsorption and precipitation processes from the water column. The implications of these results emphasize the importance of regular environmental monitoring and mitigation of pollution sources to prevent further impacts on the stability of coastal ecosystem.